Dinamika Pertumbuhan Ekonomi, Kepadatan Penduduk, dan Peran Sektor Pertanian dalam Mengentaskan Kemiskinan - Siswantoro, Ariel; Gandhi, Eko Atmayudi (Ecoplan, 2025)
Poverty is an ongoing challenge faced by every country. In Indonesia, the agricultural sector – despite being a productive sector crucial to economic growth – is still associated with high poverty rates. Provinces with the highest poverty rates are dominated by those with the highest role in the agricultural sector, such as NTT, Maluku, Gorontalo, Aceh, and Bengkulu. Other factors that are said to have effects on poverty are population density and economic growth. In fact, economic growth can be accelerated to overcome poverty. The purpose of this study is to analyze the effect of economic growth, population density, and agricultural sector on poverty levels in provinces based on agricultural sector areas in Indonesia for the period 2014-2023. The study applied the panel data method with the fixed effect model. The variables were economic growth, population density, contribution of the agricultural sector, and poverty. The data were collected by taking a sample of five provinces based on agricultural sector areas in Indonesia. The results revealed that these three variables had a negative and significant effect on poverty in the studied provinces. Of the five provinces with the largest agricultural sector areas in Indonesia, the highest poverty coefficient values were recorded by NTT, Aceh, Maluku, Bengkulu, and Gorontalo.